2018
DOI: 10.3382/ps/pey337
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental boric acid does not prevent the development of footpad dermatitis in broilers subjected to high stocking density

Abstract: The present study was conducted to evaluate the protective effect of dietary boric acid supplementation on the development of incidence and severity of footpad dermatitis (FPD) in broiler chickens subjected to normal or high stocking densities (NSD or HSD). A total of 576 1-day-old ROSS 308 broiler chickens were randomly allocated to 4 treatments (8 replicate pens per treatment) in a 2 × 2 factorial arrangement of dietary boric acid (0 and 60 mg/kg) and stocking density (NSD 14 birds/m2 and HSD 22 birds/m2). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Previous studies found that HSD decreases the feed intake of broilers (Wang et al, 2014;Madilindi et al, 2018;Cengiz et al, 2018;Sanchez-Casanova et al, 2019;Magnuson et al, 2020;McKeith et al, 2020); however, scanty literature was reported about the mechanism of this action. Hypothalamus plays a critical role in the appetite regulation (Harrold et al, 2012;Everaert et al, 2019).…”
mentioning
confidence: 99%
“…Previous studies found that HSD decreases the feed intake of broilers (Wang et al, 2014;Madilindi et al, 2018;Cengiz et al, 2018;Sanchez-Casanova et al, 2019;Magnuson et al, 2020;McKeith et al, 2020); however, scanty literature was reported about the mechanism of this action. Hypothalamus plays a critical role in the appetite regulation (Harrold et al, 2012;Everaert et al, 2019).…”
mentioning
confidence: 99%
“…Ghanima et al [2] reported that a high stocking density has a negative impact on performance indicators of broiler chickens. A high stocking density deteriorates litter and air quality by increasing litter moisture and the volatilization of ammonia, which negatively affects growth performance during the grower stage due to the increasing size of chickens [31]. In addition, the disruption of gut microbial ecology that supports digestion, absorption, and production of beneficial molecules may contribute to poor growth performance of broiler chickens raised at 22-42 and 1-42 days of age at high stocking density [32].…”
Section: Discussionmentioning
confidence: 99%
“…Cengiz et al (2018) found that an increase in stocking density leads to a positive economic effect, ensuring that it does not exceed the optimal range from 34 to 40 kg/m 2 with an average final body weight of 2.5 kg.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, serum corticosterone and proinflammatory metabolites were increased. Cengiz et al (2018) found that an increase in stocking density leads to a positive economic effect, ensuring that it does not exceed the optimal range from 34 to 40 kg/m 2 with an average final body weight of 2.5 kg. Yin et al (2017) showed that with an increase in stocking density from 2 to 6 heads/m 2 , the live weight of geese at the age of 42 days ( p < 0.001) and 70 days decreased by 10.53% and 10.43%, respectively.…”
mentioning
confidence: 99%